Global Innovation Indicators analysed by multicriteria decision - Silva, Marcela do Carmo (2020)
Goal: This paper analyses how European countries of Global Innovation Indicators (GII) present in the ranking by multicriteria support aid analysis. Design / Methodology / Approach: The methodology uses Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for ranking countries and PROMETHÉE (Preference Ranking Organisation Method for Enrichment Evaluations) for outranking them. Results: There was change in 30 ordered positions from 39 countries observed. At non-compensatory method the overrating become “easier” than the compensatory method, especially when there are many alternatives and criteria for computing with small difference among values. Limitations of the investigation: It is only used the GII 2015 Europe for continuing investigations about MCDA realized for Latin America (2017) and Asia and Africa (2019). Practical implications: The applications result in a different understanding about TOPSIS ranking application, from original score list at GII; and also the perception of organized groups at outranking application. Originality / Value: Observing GII via MCDA is possible to see changing’s in the ranking according to countries profiles different from GII raking. Although European profiles seem to be similar, it is important to observe other perspective of grouping by them; suggesting quantitative studies inclusion and innovative trends.